2 Pre-hospital direct ambulance transfer has led to major improvements in timeliness of ppci in suspected stemi: temporal trends over an eight-year period in a designated PPCI centre. (6th October 2022) - Butt, Z; McGrath, B; Cadogan, D; Casserly, I; McCann, H; O'Neill, J; Keelan, E; Keelan, P; Galvin, J; Doyle, B; Blake, G
Abstract : Background: The optimal reperfusion service (ORS) protocol is a national strategy introduced in 2013 to standardize the pre-hospital care pathway for patients with ST-elevation myocardial infarction (STEMI). This protocol aimed to increase the proportion of STEMI cases directly transferred to designated primary percutaneous coronary intervention (PPCI) centres via ambulance. This evidence-based approach was implemented to improve the first-medical contact (FMC) to balloon time for STEMI cases in Ireland, as timeliness of PPCI at a national level was relatively poor as compared to international standards. Aims: To analyse temporal trends in STEMI cases arriving directly to Mater Misericordiae University Hospital (MMUH), a designated PPCI centre, following introduction of the ORS protocol; to compare FMC-to-balloon times and proportion of timely PPCI between STEMI cases arriving to MMUH via direct ambulance transfer (DAT) versus inter-hospital transfer (IHT). Methods: We obtained retrospective data from our hospital's STEMI database of all cases referred for PPCI between January 1st 2013 and December 31st 2020. We used the hospital's electronic record to obtain details of mode of referral, final diagnosis, and timeliness of interventions. Timely PPCI was defined as <120 minutes. Data from 2014 was unavailable. Results: Completed data on 2525 patients referred for PPCI to MMUH between 2013 and 2020 was collected. 2126 (84%) were ultimately diagnosed with STEMI. 1817 (85%) confirmed STEMI's had FMC within 12 hours of symptom onset and underwent PPCI. Of these 1817 PPCI's, 1289 (71%) were timely. As shown in figure 1 . There was an overall gradual temporal increase in the proportion of patients arriving to MMUH via direct ambulance transfer (42% in 2013 vs. 58% in 2020, p < 0.0001). Concurrently, there was a temporal increase in timely PPCI rate (64% in 2013 vs. 76% in 2020, p = 0.004). When patients arriving via DAT were compared with those referred via IHT ( figure 2 ), there was improvement in all measured outcomes, which was consistent for all years analysed in this audit. In 2020, 232 (58%) cases were referred via DAT, while 134 (34%) arrived via IHT. The remaining 32 (8%) cases included patients who self-presented to MMUH, or were referred directly by their general practitioner. When comparing cases arriving via DAT versus via IHT in 2020, there was a significant increase in the proportion of timely PPCI (83% vs. 56%, p < 0.0001) and a significant improvement in median FMC-to-balloon time [85 minutes (IQR 62 to 110) vs. 108 minutes (IQR 82 to 166), p < 0.0001] among the DAT group. Conclusions: There has been significant improvements in the proportion of patients with a pre-hospital presumptive diagnosis of STEMI arriving to MMUH via DAT since the introduction of the ORS protocol in 2013. DAT is associated with improved timeliness of PPCI and mean FMC-to-balloon times, when compared to IHT of suspected STEMI cases. While improvements have been made, there is still room for further optimization of the pre-hospital care pathway of suspected STEMI cases as a large proportion (42% in 2020) of cases did not arrive via DAT to MMUH.